Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Kognitif Bahasa Madura Kelas IV SDN Tengket 1 - Nisa', Mutiatun; Mardiyana, Isna Ida (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this research is to look at the use of the student team achievement division (STAD) type cooperative learning model as an effort to improve learning outcomes in Madurese language subjects, namely